2020
DOI: 10.1111/itor.12915
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of original equipment manufacturer's optimal remanufacturing mode and engagement strategy

Abstract: This study considers an original equipment manufacturer (OEM) who (a) relies on a contract manufacturer (CM) to produce its new products, and (b) engages the CM again or an independent remanufacturer (IR) to perform the remanufacturing operations of branded patented products through either authorization or outsourcing. This study chiefly investigates the optimal remanufacturing engagement strategy (i.e., engage a CM or an IR) and remanufacturing mode (i.e., authorization and outsourcing) that should be taken b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…Zhou, et al [13] investigated an OEM's remanufacturing authorization decision when competition exists in the secondary market. Zhou and Yuen [19] examined an OEM's remanufacturing partner selection over two remanufacturing modes: authorization and outsourcing, and identified OEM's and IR's preference over these two modes. Jin, et al [41] considered dealer authorization mode where an OEM can turn an IR into an authorized seller that sells both new and remanufactured products and found that remanufacturing authorization between an OEM and an IR depends on the improvement of customers' willingness to pay for the remanufactured products because of the authorization cooperation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhou, et al [13] investigated an OEM's remanufacturing authorization decision when competition exists in the secondary market. Zhou and Yuen [19] examined an OEM's remanufacturing partner selection over two remanufacturing modes: authorization and outsourcing, and identified OEM's and IR's preference over these two modes. Jin, et al [41] considered dealer authorization mode where an OEM can turn an IR into an authorized seller that sells both new and remanufactured products and found that remanufacturing authorization between an OEM and an IR depends on the improvement of customers' willingness to pay for the remanufactured products because of the authorization cooperation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remanufacturing engineering is designed to repair the used products in such a way that the qualities of the remanufactured products can meet or exceed those of new products. Recent studies have shown that product remanufacturing can increase the demand for remanufactured products, affect the production quantities of new products, and further enable the manufacturer and the whole supply chain to obtain better production methods from the manufacturer recycling model [ 5 , 6 , 7 , 17 ]. The main processing method for remanufacturing products is called authorized remanufacturing, in which the original equipment manufacturer (OEM) is only responsible for selling new products; after charging third party remanufacturers (3PR) an authorization fee, the recycling, remanufacturing, and sale of the remanufactured products are authorized to 3PR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the actual production process, the method to obtain a license for remanufacturing has become the most significant issue for remanufacturers. In foreign countries, the ink cartridge remanufacturers of Canon and Epson faced the risk of being litigated by Lexmark for remanufacturing without its permission [ 17 ]. To study these issues in great depth, this paper focuses on the equilibrium of the CLSC network considering the OEM’s in-house remanufacturing and authorized remanufacturing strategy choices.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) find that when parallel importation occurs, the manufacturer may have the motivation to license the technology and reduce the unit licensing fee. Zhou and Yuen (2021) investigate that the optimal remanufacturing mode (i.e., authorization and outsourcing) should be taken by an original equipment manufacturer. Yang et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2021) find that when parallel importation occurs, the manufacturer may have the motivation to license the technology and reduce the unit licensing fee. Zhou and Yuen (2021) investigate that the optimal remanufacturing mode (i.e., authorization and outsourcing) should be taken by an original equipment manufacturer. Yang et al (2019) investigate whether and how a patent-holding supplier should license its technology patent to a potential rival when both suppliers face the supply disruptions.…”
Section: Literature Reviewmentioning
confidence: 99%